1980
DOI: 10.1128/jvi.36.3.719-733.1980
|View full text |Cite
|
Sign up to set email alerts
|

Translational control of protein synthesis after infection by vesicular stomatitis virus

Abstract: Four hours after infection of BHK cells by vesicular stomatitis virus (VSV), the rate of total protein synthesis was about 65% that of uninfected cells and synthesis of the 12 to 15 predominant cellular polypeptides was reduced to a level about 25% that of control cells. As determined by in vitro translation of isolated RNA and both one-and two-dimensional gel analyses of the products, all predominant cellular mRNA's remained intact and translatable after infection. The total amount of translatable mRNA per ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
50
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 42 publications
9
50
0
Order By: Relevance
“…(3) Jaye et al (1982); Lodish and Porter (1980); Nisbioka and Silverstein (1978a). (4) Lodish and Porter (1980); Otto and Lucas-Lenard (1980). (5) Francoeur and Stanners (1978); .…”
Section: A Cautionary Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Jaye et al (1982); Lodish and Porter (1980); Nisbioka and Silverstein (1978a). (4) Lodish and Porter (1980); Otto and Lucas-Lenard (1980). (5) Francoeur and Stanners (1978); .…”
Section: A Cautionary Notesmentioning
confidence: 99%
“…Whereas reovirus mRNAs appear to be less efficient than most host mRNAs, VSV mRNAs are probably translated as efficiently as host mRNAs, but not more so. Competition is simply proportional to the concentration of viral mRNAs in the cytoplasm (Lodish and Porter, 1981),8 and VSV and host mRNAs that encode the same-sized proteins are on polysomes of the same size (Lodish and Porter, 1980). In some cell lines infected by some strains of VSV, a portion of the eIF-2 pool seems to be inactivated (Centrella and Lucas-Lenard, 1982;Dratewka-Kos et al, 1984).…”
Section: Competition By Mrna Abundancementioning
confidence: 99%
“…Metabolic labeling studies demonstrate that 4 hours post VSV infection of baby hamster kidney cells in culture, total translation is suppressed to about 65% the level of uninfected controls [39]. Extraction of mRNA from infected cells coupled with its in vitro translation confirmed that the cellular mRNAs remain intact and are competent for translation [39].…”
mentioning
confidence: 94%
“…Guanine-N-7 (G-N-7) methylation of the mRNA cap structure is required for recognition of the cap by the rate-limiting factor for translation initiation, eIF-4E (28)(29)(30). Although the precise mechanism by which VSV mRNAs are translated is not fully understood, they utilize a variation of the canonical cap-dependent translational pathway that is hypersensitive to the lack of a ribosomal protein, rpL40 (30)(31)(32)(33)(34). In infected cells, host mRNA translation is rapidly inhibited through suppression of the intracellular pools of eIF-4E by a manipulation of the phosphorylation status of the 4E binding protein (4E-BP1) (35).…”
mentioning
confidence: 99%
“…In infected cells, host mRNA translation is rapidly inhibited through suppression of the intracellular pools of eIF-4E by a manipulation of the phosphorylation status of the 4E binding protein (4E-BP1) (35). Nevertheless, in vitro experiments have shown that G-N-7 cap methylation facilitates translation of VSV mRNA (30,31,33,34). The biological function of mRNA cap 2=-O methylation, however, remains less well understood.…”
mentioning
confidence: 99%